Deskripsi Pemahaman Konsep Geometri Bidang Berdasarkan Gaya Belajar Visual Auditori Kinestetik Siswa Kelas VII - Bernard, Bernard; Asdar, Asdar; Muslim, Amila Akrama (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2024)
This is a descriptive research which depicts essentially the object and explains more detail and systematic about student’ conceptual understanding on plane geometry towards the students who have visual, auditory, kinesthetic studying style. The subject was selected based on the questionnaire which was deployed in a class, which consists of 28 students, at SMP Muhammadiyah Watansoppeng. In the process, there were 3 steps; first, giving information about the goal of research and once in a while giving the questionnaire of studying style. Second, giving the test and doing observation step. Third, doing interview in order to know more information about how the students answer the problems on the test. The used instruments were the researcher, questionnaire of studying style, test of plane geometry-concept comprehention, and interview outlines. The result of this research showed that a student with visual-studying style was sufficiently able to meet two of five indicators demand which had been determined. But the student with auditory-studying style unable to meet the five indicators demand which had been determined